Application of Augmented Reality for Accurate Punctures During Stage 1 Sacral Neuromodulation - Yuan, Haoyu; Xiao, Yuansong; Lin, Xiaoyu; Zhang, Lei; Yang, Chenglin; Hu, Zhengfei; Yang, Yue; Wu, Peixian (International neurourology journal, 2024)
Purpose: Precise electrode placement is crucial for the success of sacral neuromodulation (SNM). The aim of this study was to explore a more accurate and convenient method for positioning punctures during the first stage of SNM.Methods: This retrospective study compared preoperative baseline values, intraoperative indicators, postoperative scores, and other clinical data from 130 patients who underwent SNM electrode implantation at our department between 2018 and 2023. The patients were divided into an experimental group and a control group to assess the advantages and feasibility of augmented reality (AR)-guided sacral nerve electrode implantation.Results: The experimental group experienced fewer intraoperative puncture attempts and achieved more accurate AR-guided localization punctures. Additionally, there were more responsive electrode contact points (2.74±0.51 vs. 2.46±0.74) and a lower initial voltage postimplantation (1.09±0.39 V vs. 1.69±0.43 V). The number of intraoperative x-ray fluoroscopies was significantly lower in the experimental group than in the control group (5.94±1.46 vs. 9.22±1.93), leading to a shorter overall operation time (61.32±11.27 minutes vs. 83.49±15.84 minutes). Furthermore, there was no need for additional local anesthetic drugs during the surgery in the experimental group. Comparative observations revealed no significant differences in intraoperative blood loss or the sacral hole location for electrode implantation between the 2 groups. Although the incidence of wound infection and the rate of permanent implantation in stage 2 were similar in both groups, the pain score on the first day postoperation was significantly lower in the experimental group than in the control group (2.62±0.697 vs. 2.83±0.816).Conclusions: AR-guided sacral nerve modulation implantation can reduce both the number of punctures and the duration of the operation while ensuring safety and effectiveness. This technique can enhance the contact points of the response electrode, effectively lower the initial response voltage, and stabilize the electrode.